The effects of a 6-week plyometric training on muscular strength performance in silat exponents (Revista de Artes Marciales Asiáticas, 2019)
The aim of this study was to investigate the effect of 6-week plyometric training on muscular strength in young silat athletes. Thirty-four male silat exponents (Mage = 14 ± 3.22 years) were randomly assigned to a control or experimental group (n = 17 for each group). The experimental group participated in conventional silat workout routine three times a week for one-hour session plus plyometric training two times a week for one-hour session. The control group performed conventional silat workout routine three times per week for one to two-hours session. The one repetition maximum (1RM) squat test was used three times (pre-, mid- and post-test). Results revealed that muscular strength performance improved for the experimental group. This improvement was 9.16% between pre- and mid-test, 18.81% between mid- and post-test, and 29.7 % between pre- and post-test. Plyometric training was shown to be effective to improve maximum strength of young silat athletes.